Phenoxy acetophenones, Aromatic aldehyde, Phenoxy acetophenone, Antiinflammatory activity. - SINGH, DAROGA; PRAKASH RAI, BISHWA; SINGH, VANDANA (Asian Journal of Chemistry, 2010)
Dimethyl formaminium chloride chlorosulphate, a stable complex formed from sulphuryl chloride/dimethyl formamide and its synthetic utility in the preparation of different cephem antibiotics described.